Avoiding the planning support system pitfalls? What smart governance can learn from the planning support system implementation gap. (October 2020) - Jiang, Huaxiong; Geertman, Stan; Witte, Patrick
The implementation of smart governance in government policies and practices is criticised for its dominant focus on technology investments, which leads to a rather technocratic and corporate way of 'smartly' governing cities and less consideration of actual user needs. To help prevent a mismatch between the demand for and the supply of technology, this paper explores what smart governance can learn from efforts in debates on planning support systems to close the 'PSS implementation gap'. This gap refers to a long-standing discrepancy between the availability of planning support systems (supply) and the time-bound support needs of planning practice (demand). By exploring both the academic field of smart governance and the debates on the planning support system implementation gap, this paper contributes to the further development of smart governance by learning from the experiences in the planning support system debates. Two particular lessons are distilled: (1) for technology to be of added value to practice, it should be attuned to the wishes and capabilities of the intended users and to the specifics of the tasks to be accomplished, given the particularities of the context in which the technology is applied; and (2) closing the planning support system implementation gap reveals that knowledge on the context specificities is of utmost importance and will also be of importance to the smart governance developments. In conclusion, smart governance can and should become more aware of the role of contextual factors in collaboration with users and urban issues. This is expected to shift the emphasis from today's technology-focused, supply-driven smart governance development, to a socio-technical, application-pulled and demand-driven smart governance development.